Construction of an enteral nutrition evaluation system for critically ill patients based on the Delphi method - Yanrong Yao; Jingli Liu; Hongmei Xue; Xiaoyan Wang; Weijie Yao; Na Liu; Zuozheng Wang; Guangli Mi (The Saudi Journal of Gastroenterology, 2024)
Background: This study aimed to construct an enteral nutrition evaluation system for critically ill patients using the Delphi method to direct the formulation of enteral nutrition support strategies and reduce interruption to enteral feeding. Methods: We used domestic and foreign databases to obtain and analyze the literature and form “The Whole-Proceeding Enteral Nutrition Evaluation System for Critically Ill Patients.” The Delphi method was used to conduct two rounds of expert opinion consultation, combined with the suggestions from the research group to finalize the nutrition evaluation content of the system. Results: After two rounds of expert consultation, a nutrition evaluation system was formed around three dimensions: before the start, during, and after the end of nutritional support. The effective recovery rates of the two rounds of expert consultation were 90.0% (18/20) and 100.0% (18/18), respectively. Authority coefficients were 0.865 and 0.908, while Kendall coordination coefficients were 0.108 (P < 0.05) and 0.115 (P < 0.001), respectively. Finally, the full enteral nutrition evaluation system for critically ill patients was constructed based on the Delphi method, including three primary items and seven secondary and 28 tertiary indicators. Conclusion: The established “Whole-Proceeding Enteral Nutrition Evaluation System for Critically Ill Patients” has high consistency from expert opinions and reliability, which can provide a practical evaluation tool for the process of enteral nutrition for severe patients.